GUMSA framework for the development of mobile learning system of a malay language using near field communication - Mustafa, Mamat; Yahaya Garba, Shawai; Noor Maizura, Mohamad Noor (Hikari Ltd., 2015)
Discovering a city during vacation, a tourist might learn foreign language from a travel internet site on a home desktop computer, phone and interactive multimedia guide on the tourist information. The combination of these experiences constitutes mobile language learning. This paper present a mobile learning framework to develop a Malay language learning application using near field communication (NFC) technology. The proposed framework follow the lifelong mobile learning framework approach with some modification and added features; Mobile learning activity design which constitute Requirement and constraint analysis, technology environment design, mobile learning scenario and learning support services.